From the Halls of the Montezumas : Mexican War Dispatches from James L. Freaner, Writing under the Pen Name "Mustang" - Mustang (War correspondent), 1817-1852 (Book collections on Project MUSE., 2019)
James L. Freaner is one of the most important unknown Americans in our nation's history. Freaner gained fame throughout the country during the Mexican War while covering General Winfield Scott's campaign. As one of America's first war correspondents, Freaner's letters appeared in newspapers under the byline ""Mustang, "" and his reports from the front included information unavailable elsewhere. Among Freaner's scoops were the publication of complete casualty lists (long before official reports became public), detailed battle descriptions, and observations on postwar Mexico. Despite his widespre.